2019
DOI: 10.1038/s41598-019-44400-2
|View full text |Cite
|
Sign up to set email alerts
|

Top-down Effects on Empathy for Pain in Adults with Autistic Traits

Abstract: While empathic responses of individuals with autism-spectrum disorder have been reported to be modulated by top-down attention, it remains unclear whether empathy for pain in typically developing individuals with autistic traits also involves such top-down modulation mechanisms. This study employed the autism-spectrum quotient (AQ) to quantify autistic traits in a group of 1,231 healthy adults. Two subset groups (High-AQ and Low-AQ groups) were randomly selected from the highest and lowest 10% AQ scores respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 40 publications
8
57
0
Order By: Relevance
“…In addition, the effects of the modulation of top-down attention on the empathic abilities of individuals with autistic traits have also been studied. In line with previous studies 7,8 , our previously published study explored top-down attention for others' pain, which was manipulated by instructing participants to either focus on pain cues in the stimuli, or to focus on non-pain cues 16,17 . The results showed that if individuals with autistic traits were not explicitly instructed to focus on others' feelings, their empathic responses show impairments 16,17 .…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…In addition, the effects of the modulation of top-down attention on the empathic abilities of individuals with autistic traits have also been studied. In line with previous studies 7,8 , our previously published study explored top-down attention for others' pain, which was manipulated by instructing participants to either focus on pain cues in the stimuli, or to focus on non-pain cues 16,17 . The results showed that if individuals with autistic traits were not explicitly instructed to focus on others' feelings, their empathic responses show impairments 16,17 .…”
mentioning
confidence: 93%
“…In line with previous studies 7,8 , our previously published study explored top-down attention for others' pain, which was manipulated by instructing participants to either focus on pain cues in the stimuli, or to focus on non-pain cues 16,17 . The results showed that if individuals with autistic traits were not explicitly instructed to focus on others' feelings, their empathic responses show impairments 16,17 . Furthermore, previous studies indicated that during passive viewing, ASD individuals did not show empathic responses until they were explicitly instructed to do so; this suggests that in these individuals, the spontaneous empathic response may be impaired 29,30 .…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…emotions in the faces, such that negative emotions suppressed attractiveness assessments as compared to positive and neutral emotional faces 19,20 . According to the "threat value of pain" hypothesis, others' pain, serving as warning signals to avoid or escape [5][6][7][8] , would elicit negative emotional reactions [21][22][23][24] , thus suppressing the perception of physical attractiveness, as evidenced by decreased attractiveness ratings and neural responses.…”
mentioning
confidence: 99%